MICROENCAPSULATION OF OXOLINIC ACID WITH CHITOSAN BEADS - Cárdenas-Triviño, Galo; Burgos, Marianela; Von Plessing, Carlos (Journal of the Chilean Chemical Society, 2019)
Chitosan microspheres were synthesized by the method of ionic gelling. The oxolinic acid was encapsulated in chitosan microspheres with different concentrations, which was corroborated by FT-IR of the spheres showing typical bands of chitosan and the antibiotic. The inclusion of antibiotic in the microspheres, was determined by means of thermogravimetry since there were two decompositions temperatures corresponding to different compounds. At several concentrations of oxolinic acid chitosan microspheres had different external morphology, by means of SEM was observed that a high concentration of antibiotic generated smooth external texture, where most of them were spherical shape. The solubility of chitosan microspheres was very low in sea and nanopure water, since the protonation at basic pH of chitosan amino group was very low, the solubility was lower than diluted acetic acid. The solubility of chitosan at different concentrations of antibiotic microspheres showed a Gaussian tendency of solubility at different acid pH ranges (hydrogels). The optimum pH of chitosan spheres solubility occurred at pH 3.5, which was observed at maximum point of curve. Chitosan microspheres had different concentrations of oxolinic acid, because releasing of antibiotic concentration may occur and which was measured by the HPLC method. The percentage of encapsulation of microspheres was high, being all of them greater than 90%. The release of oxolinic acid on chitosan microspheres was faster at pH 5.7, where the first releases were at 30 minutes after the test begins, instead at pH 7.5 was slower. Chitosan microspheres had an average dry weight of 1.1x10-3 mg.